Comparison of cultural and immunological methods for the evaluation of foodborne intoxications risk caused by staphylococcus aureus in white cheese, raw milk, minced meat and inegol meatball - Nihat Telli; Nuray Gamze Yörük; Arife Ezgi Telli; Muhammed Ali Cebirbay; Ahmet Güner (Eurasian Journal of Veterinary Sciences)
Aim: The objective of this study was to analyze the physical, chemical and microbiological quality of white cheese, raw milk, ground meat and İnegöl meatballs and to determine the contamination of Staphylococcus aureus (S. aureus) and presence its toxin. Materials and Methods: A total of 200 samples including white cheese (n=50), raw milk (n=50), ground meat (n=50) and İnegöl meatballs (n=50) were collected. The samples were evaluated in terms of classical cultural microbiological methods total mesophilic aerobic bacteria (TMAB), total psychrophilic aerobic bacteria (TPAB), coliform, lactic acid bacteria (LAB) and S. aureus], physical and chemical analyzes (pH, acidity and, dry matter). The presence of staphylococcal enterotoxins (SEs) was investigated using the VIDAS Staph enterotoxin kit based on enzymelinked fluorescent immunoassay (ELFA). Results: Average pH values in raw milk, white cheese, minced meat and İnegöl meatballs were 6.53, 4.82, 5.99 and 6.63; dry matter values were 12.51%, 37.71%, 38.97%, 49.70%, and the total lactic acidities were 0.16%, 0.67%, 0.08% and 0.40%, respectively. TMAB (4.53-9.86 log10CFU/g-ml), TPAB (3.39-7.69 log10CFU / g-ml), coliform bacteria (2.04-8.53 log10CFU/gml), LAB (2.90-7.64 log10CFU/g-ml) and S. aureus (2.61-6.46 log10CFU/g-ml) were counted across a wide range. SEs was detected in 1 (2%) of İnegöl meatball samples and 29 (58%) of ground meat samples. Conclusion: Since all strains of S. aureus are not responsible for the production of SEs, it should be considered to detect the SE together with cultural methods in the evaluation of staphylococcal food intoxications and production of safe food.